Re-introducing the Cambridge Group Family Reconstitutions - George Alter; Gill Newton; Jim Oeppen (Historical Life Course Studies)
English Population History from Family Reconstitution 1580–1837 was important both for its scope and its methodology. The volume was based on data from family reconstitutions of 26 parishes carefully selected to represent 250 years of English demographic history. These data remain relevant for new research questions, such as studying the intergenerational inheritance of fertility and mortality. To expand their availability the family reconstitutions have been translated into new formats: a relational database, the Intermediate Data Structure (IDS) and an episode file for fertility analysis. This paper describes that process and examines the impact of methodological decisions on analysis of the data. Wrigley, Davies, Oeppen, and Schofield were sensitive to changes in the quality of the parish registers and cautiously applied the principles of family reconstitution developed by Louis Henry. We examine how these choices affect the measurement of fertility and biases that are introduced when important principles are ignored.